A multidisciplinary approach of workload assessment in real-job situations: investigation in the field of aerospace activities - Mélan, Claudine; Cascino, Nadine (Frontiers in Psychology, 2014)
The present contribution presents two field studies combining tools and methods from cognitive psychology and from occupational psychology in order to perform a thorough investigation of workload in employees. Cognitive load theory proposes to distinguish different load categories of working memory, in a context of instruction. Intrinsic load is inherent to the task, extraneous load refers to components of a learning environment that may be modified to reduce total load, and germane load enables schemas construction and thus efficient learning. We showed previously that this theoretical framework may be successfully extended to working memory tasks in non instructional designs. Other theoretical models, issued from the field of occupational psychology, account for an individual’s perception of work demands or requirements in the context of different psychosocial features of the (work) environment. Combining these approaches is difficult as workload assessment by job-perception questionnaires explore an individual’s overall job-perception over a large time-period, whereas cognitive load investigations in working memory tasks are typically performed within short time-periods. We proposed an original methodology enabling investigation of workload and load factors in a comparable time-frame. We report two field studies investigating workload on different shift-phases and between work-shifts, with two custom-made tools. The first one enabled workload assessment by manipulating intrinsic load (task difficulty) and extraneous load (time pressure) in a working-memory task. The second tool was a questionnaire based on the theoretical concepts of work-demands, control and psychosocial support. Two additional dimensions suspected to contribute to job-perception, i.e. work-family conflicts and availability of human and technical resources were also explored. Results of workload assessments were discussed in light of operators’ alertness and job-performance.